Analisis Filosofis Larangan Riba dalam Tinjauan Maqashid Al-Shariah untuk Mewujudkan Keadilan Ekonomi - Hanif, Khairul; Mawardi (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
Usury is strictly prohibited in Islam. The prohibition of usury in Islam aims to create a fair and just economic system. As the main normative principle in Islamic law, maqashid sharia emphasizes the protection of five basic aspects, namely religion (hifz al-diin), soul (hifz al-nafs), reason (hifz al-aql), descendants (hifz al-nasl), and property (hifz al-maal). This study uses a qualitative method with a library research approach. The data collection technique in this study, the author uses documentation. The results of the analysis of the five aspects of maqasid al-shari'ah in the prohibition of usury confirm that the prohibition is not only normative, but also has deep moral, social, and economic dimensions. The prohibition of usury in Islam not only protects individuals from financial exploitation, but also ensures that the economic system runs in accordance with the principles of justice, balance, and common welfare which are the core of maqasid al-shari'ah.